Maragang hill trekking through community based ecotourism (cbe): the tourist guides responsibility and challenges in Kundasang, Sabah, Malaysia - Nevashiny Karuppiah; Rosazman Hussin; Jalihah Md Shah; Normah Abdul Latip; Teuku Afrizal Teuku Anuar (Scopus, 2022)
The issue of this article is tourist guides’ responsibility and the challenges they face when conducting Maragang Hill trekking activities through communitybased ecotourism (CBE) in Kundasang, Sabah. This study used mixed data collection methods: in-depth interviews with eight informants and observations around Mesilou village and at Maragang hill. The survey was also conducted on 63 community members in Maragang Hill as a supporting method to obtain more accurate data. Secondary sources refer to reinforce the study data. The concepts used in this study are interrelated to the topic and to understand the issue deeply. The results of this study have shown that although tourist guides did their responsibility perfectly (such as providing additional information to the tourists, a safety briefing, giving information about flora and fauna to the tourists, and hiking rules), some of the challenges remain for them. This study indicates the challenges tourist guides face while conducting Maragang Hill trekking activities through community-based ecotourism. This study enhances the concept of CBE in studies related to ecotourism activities, especially ecotourism based on nature. In so doing, the result of this study reduces the challenges faced by tourist guides or CBE management while conducting Maragang Hill-related activities soon.